Mothers Attitudes toward Non-Nutritive (Pacifier) Sucking Habits in Their Children - Nazar Ramadhan Authman; Kareema Ahmad Hussein (Kufa Journal for Nursing Sciences)
Objectives: The main objective of the present study is to assess the mother's attitude toward pacifier habits in their children.